Simultaneous Synthesis and Characterization of Quinolinates to Obtain Cobalt Ferrite - Alessandro Retizlaf; Mariana de Souza Sikora; Sirlei Dias Teixeira; Henrique Emilio Zorel Junior; Giancarlo Botteselle (Orbital: The Electronic Journal of Chemistry, 2024)
8-Hydroxyquinoline and its derivatives are compounds with a variety of applications in various fields of knowledge such as medicine, biological sciences, and chemistry. Many of these applications are possible because 8-hydroxyquinoline forms stable and insoluble metal chelates with a range of metals such as copper, cobalt, calcium, iron, and nickel. One of the possible applications of 8-HQ chelates is the production of metal oxides by thermal decomposition, however, there are few studies in the literature using quinolinates for this purpose. If the chelates are synthesized simultaneously, it is possible to obtain double oxides such as cobalt ferrite, which has numerous applications due to its magnetic properties. In this way, the present work aims to the simultaneous synthesis of cobalt II and iron III quinolinates at different pH values, as well as their characterization by XDR, SEM, TEM, FTIR and Raman analysis. Finally, the quinollinate synthetized were applied as precursors to obtain cobalt ferrite by thermal decomposition.